2023
DOI: 10.29300/disastra.v5i1.8123
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Pembelajaran Keterampilan Berbahasa Anak Menggunakan Algoritma Aplikasi Tiktok, Instagram Reels, dan Youtube Shorts

Abstract: A phenomenon that is often seen is that children really like to play and watch videos via cellphones. However, Tiktok and similar applications are not educational special applications, there are many videos that are displayed without any filters. So that it can cause the possibility of videos that children watch are videos that are not good and not suitable for children to watch. Therefore, it is necessary to understand and tricks for utilizing application algorithms so that learning strategies can run well. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…A previous study found that TikTok online videos are used for learning pronunciation, grammar, vocabulary, common mistakes, and English facts (Warini et al, 2020). While on Instagram, English learning uses the Reels feature with attractive packaging (Malik, 2023).…”
Section: "I Think the Utilization Of Edtech Or Technology For Learnin...mentioning
confidence: 99%
“…A previous study found that TikTok online videos are used for learning pronunciation, grammar, vocabulary, common mistakes, and English facts (Warini et al, 2020). While on Instagram, English learning uses the Reels feature with attractive packaging (Malik, 2023).…”
Section: "I Think the Utilization Of Edtech Or Technology For Learnin...mentioning
confidence: 99%